Pathogenic bacteria in raw milk and milk products in Ethiopia: A decade review of prevalence, contributing factors, and antimicrobial resistance. A systematic review and meta-analysis - Sifray Batire Belayneh; Chuol Kulang Luak; Samuel Alemu Bamboro (SAGE Open Medicine)
Background: Foodborne illnesses pose significant health challenges globally, affecting both developed and developing nations. Despite numerous review addressing pathogenic bacteria in various animal-origin foods in Ethiopia, there is a notable lack of research specifically focused on raw milk and milk products. Objective: This study aims to systematically review the prevalence of pathogenic bacteria in raw milk and milk products, identify associated risk factors and assess antimicrobial resistance in Ethiopia from 2014 to 2024. Methods: A comprehensive search of PubMed, JANE, Scopus, and Google Scholar yielded 1596 articles, of which 18 full-text studies were included based on eligibility criteria, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data were extracted and analyzed to determine pooled prevalence rates, associated risk factors, and antimicrobial resistance across various Ethiopian regions. Results: The review identified a pooled prevalence of pathogenic bacteria at 18.7% (95% CI: 17.46%–19.94%) from January 2014 to February 2024. Major pathogens included Escherichia coli O157:H7 (5.2%), Staphylococcus aureus (18.27%), and Listeria monocytogenes (3.86%). The Oromia Region exhibited the highest prevalence (85.9%), while the lowest was recorded in Ambo, Holeta, and Bako towns (2.28%). Bacterial contamination of raw milk and milk product showed a statistically significant association with raw milk sample collectors ( p  < 0.028), livestock age ( p  < 0.001), inadequate hygiene ( p  < 0.0001), and illiteracy ( p  < 0.000), highlighting urgent educational needs. The overall antimicrobial resistance rate was alarming at 86.2%, with multidrug resistant isolates constituting 50.6%. Significant resistance was noted against commonly used antimicrobials such as nalidixic acid (100%), ampicillin (89.7%), amoxicillin (76.3%), penicillin (75%), oxacillin (73.6%), and streptomycin (61.5%). Conclusions: The findings indicate a critical need for enhanced surveillance and intervention strategies to address microbial contamination and antibiotic resistance in Ethiopia’s dairy sector. Targeted educational initiatives and stricter regulations on antibiotic use in animal husbandry are essential to improve dairy safety and public health outcomes.